2006
DOI: 10.1063/1.2402581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidation on the chemical bonding structure of PECVD SiNx thin films

Abstract: This study investigated the effect of oxidation on the chemical bonding structures of silicon nitride thin films synthesized by a low-temperature plasma-enhanced chemical vapor deposition ͑PECVD͒ method. These films were heat treated to different temperatures up to 1373 K. The bonding structures were studied by means of x-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, and transmission electron microscopy. It was found that the amorphous PECVD SiN x films were subjected to oxidation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…It ought to be pointed out that further detailed XPS analysis indicates that amorphous SiN x in the oxidized film actually contains certain amount of oxygen, i.e. it is in fact silicon oxynitride, expressed as SiN 1−x O x [26], whereas, the crystalline SiO 2 is pure SiO 2 . The identification of the silicon oxynitride is consistent with previous studies [27].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It ought to be pointed out that further detailed XPS analysis indicates that amorphous SiN x in the oxidized film actually contains certain amount of oxygen, i.e. it is in fact silicon oxynitride, expressed as SiN 1−x O x [26], whereas, the crystalline SiO 2 is pure SiO 2 . The identification of the silicon oxynitride is consistent with previous studies [27].…”
Section: Discussionmentioning
confidence: 98%
“…5 shows the FTIR measurements of the four films. The FTIR spectra showed absorbance peaks corresponding to the N-H bond, Si-O bond and Si-N bond [3,25,26]. It is seen that the as-deposited film contained both N-H and Si-N bonds.…”
Section: Figurementioning
confidence: 96%
“…The films used in this study have previously been shown to contain no physical porosity. 21 In this regard, the large variation in can only be attributed to the large variations in atomic compositions of the films deposited under different conditions. The variations in atomic composition also affect the density of the films, as discussed.…”
Section: Discussionmentioning
confidence: 98%
“…The films deposited are found to be perfectly dense without any sign of pinholes or physical porosity. 21 In this regard, the large variation in density is attributed to significant variations in the chemical and molecular structure of the films, i.e., the films deposited at high and low temperatures are chemically different. Decreasing the deposition temperature decreases the completeness of the film deposition reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that exposure to high temperatures causes changes in the chemical composition, atomic bonding structure and film morphology of PECVD SiN x films [8][9][10][11] . In particular, crystallization is observed during high temperature heat treatment in air.…”
Section: Introductionmentioning
confidence: 99%